Collection and Analysis of data for Inter-domain Traffic Engineering - Cardona, Juan Camilo; Francois, Pierre; Lucente, Paolo (Anais do Workshop Pré-IETF (WPIETF); 2014: Anais do I Workshop Pré-IETF, 2014)
Inter-domain IP trafﬁc engineering requires the collection and analysis of data that is distributed among multiple network platforms. This process is usually considered complex for network operators and limits the efﬁciency that trafﬁc management methods can achieve. The introduction of Software Deﬁne Networks may change this rigid context, as it is pushing operators to request ﬂexible routing system architectures. In the future, the network operation team might have the resources to obtain, maintain, and analyze a rich variety of data from within and outside their networks. Without the need to change many of their routing devices, such data can be leveraged to implement more complex inter-domain TE applications. In this paper, we review the process of data collection and management required to beneﬁt from such techniques. Additionally, we describe various enhanced TE applications, providing details of one of them in a case study.